2017
DOI: 10.1186/s12884-017-1434-1
|View full text |Cite
|
Sign up to set email alerts
|

Care of the mother-infant dyad: a novel approach to conducting and evaluating neonatal resuscitation simulation training in Bihar, India

Abstract: BackgroundAs the global under-five mortality rate declines, an increasing percentage is attributable to early neonatal mortality. A quarter of early neonatal deaths are due to perinatal asphyxia. However, neonatal resuscitation (NR) simulation training in low-resource settings, where the majority of neonatal deaths occur, has achieved variable success. In Bihar, India, the poorest region in South Asia, there is tremendous need for a new approach to reducing neonatal morality.MethodsThis analysis aims to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 25 publications
0
17
0
9
Order By: Relevance
“…Across the four phases, a total of 3422 mentees were trained statewide. Through AMANAT, mentees received training in Basic Emergency Obstetric and Neonatal Care [21].…”
Section: Methodsmentioning
confidence: 99%
“…Across the four phases, a total of 3422 mentees were trained statewide. Through AMANAT, mentees received training in Basic Emergency Obstetric and Neonatal Care [21].…”
Section: Methodsmentioning
confidence: 99%
“…A semi-structured interview guide was developed and informed by initial evaluations of PRONTO simulation training in Bihar [ 21 ], demographic and health systems data from Bihar [ 17 , 22 ], and multi-country bottleneck analyses [ 7 – 11 ]. The interview guide employed open-ended questions about potential barriers while allowing the interviewer flexibility to ask additional questions on emerging themes.…”
Section: Methodsmentioning
confidence: 99%
“…Within the AMANAT intervention, PRONTO International trained mentors to teach emergency obstetric and neonatal management to ANM/GNM mentees using simulation [ 20 ]. Ongoing evaluations of PRONTO training in Bihar have demonstrated that nurse mentees’ skills in NR lag behind their skill acquisition in obstetric emergencies [ 21 ]. In response, this manuscript aims to characterize the logistical, cultural, and structural barriers to the use of EBPs in immediate neonatal care, defined as care required during the immediate transition to post-natal life, and NR.…”
Section: Introductionmentioning
confidence: 99%
“…PRONTO is a highly realistic, simulation-based obstetric and neonatal emergency training program designed for low-resource settings [ 19 , 20 ]. Simulation-enhanced mentoring was implemented in 320 PHCs across Bihar between 2015 and 2017, as described in detail elsewhere [ 21 ].…”
Section: Introductionmentioning
confidence: 99%